The Comprehensive Study of Uprisement of Patanjali Ayurveda From the Point of Contribution of Marketing Mix Strategies - Asive Khan, Dr. Mohammad (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The 10 years old FMCG Company Patanjali is the fastest growing company in India as per CLSA & HSBC data. Founded by Acharya Balkrishna and yoga guru Baba Ramdev in the year 2006 it has emerged as a prominent FMCG player in the market with a large number of products and deep assortments. Its manufacturing units are located in Haridwar and outside India i.e. Nepal under the trademark of Nepal Gramudyog. It is primarily in the business of minerals and herbal products. Yoga Guru Baba Ramdev being the promoter of the herbal products produced by Patanjali is the vital advantage that Patanjali has over any other FMCG company in India. Having more than 400 products with differing SKU’s made up of herbal and natural components are helping the company to offer bundled products to the customers. Patanjali’s objective of the business is to provide cost-effective products, superior quality products which are the crucial factor in the success of any FMCG company. Low or no advertising and promotion expenses are helping the company by keeping its prices low and make it affordable without compromising on quality.. Keywords: Small sector BPO, Large sector BPO, MNC, Corporate Culture, Mental Fatigue